Pemetaan Potensi Kerawanan Banjir Rob di Kabupaten Gianyar - I Kade Alfian Kusuma Wirayuda; I Wayan Nuarsa; I Dewa Nyoman Nurweda Putra (Department of Marine Sciences, Faculty of Marine Science and Fisheries, Udayana University, 2020)
Tidal flood is a water inundation phenomenon happened on the coast of the mainland or the coast which is caused by the tides of the sea. Tidal flood causes inundation on the certain parts of the mainland due to land altitude is lower than sea level at high tides. Some beaches around Gianyar, Bali, potentially experience a tidal flood. There is no research about tidal flood in Gianyar regency yet gives impact to the information about areas that potentially experience a tidal flood. This study aimed to determine the distribution of flood-prone areas in Gianyar Regency. Remote sensing and other spatial data by using scoring methods were utilized to determine prone areas of tidal flood. The parameters used included land elevation, distance area from shoreline, distance area from river, slope, land cover, and soil types. Result of the study shows that the 1104 ha of the total research area 66,37 ha or 6,02% are vulnerable areas, 684,51 ha or 62,00% are quite vulnerable area, and 353,12 ha or 31,98% are classified as non-prone areas. Spatial distribution of tidal flood potential in Gianyar Regency includes Rangkan Beach, around Purnama Beach, Saba Beach, Keramas Beach, Pering Beach, Lebih Beach and the west side of Siyut Beach . Observations and interviews toward vulnerable areas were conducted as the validation of the result of the study.